(untitled) (Journal of the College of Languages (JCL), 2021)
The present paper focuses on studying a rhetorical form often used in Spanish linguistic discourse .It also examines the study two sides (theoretical and practical), the concept of metaphor, the most important modern school that deals with this issue, the development of this technique and its relationship with other intellectual ideologies, and the role metaphor plays in interpreting the meaning of the linguistic discourse especially in conveying political message. The study allows the formulation and the creation of a conceptual picture for the purposes of metaphor in the linguistic discourse used in Spanish press. It investigates discursive models from the Spanish press, like the speeches of Mr. (Louis Bassets) the Spanish writer in the Spanish newspaper (El Pais), (the electronic version). The study includes an analysis of metaphorical formulas in all fields of life such as (sports, the animal world, the machine, the force or military field ... etc. or any other fields from which the linguistic metaphors are taken). The conclusion sums up the findings drawn from the study, and then the references section contains scientific and journalistic sources. Resumen Nuestra investigación se centra en el estudio de una forma retórica del uso frecuente en los discursos lingüísticos que encontramos en textos escritos en español. Nuestro trabajo de investigación aborda también las dos partes (teórica y práctica), así como explicar el concepto de la metáfora. La escuela moderna más importante que se ha ocupado de este tema es el desarrollo de esta ciencia y sus relaciones con otras ideologías intelectuales, destacando el papel de la metáfora en la interpretación del significado de un discurso lingüístico de emisor de un mensaje político. Este estudio permite hacer un cuadro conceptual a efectos de metáfora en el discurso lingüístico utilizado en la prensa en España. Durante nuestra investigación estudiaremos modelos retóricos de la prensa española, concretamente los discursos del escritor en el diario español El País, (Lluís Bassets), el escritor en la página de opinión (versión electrónica) y publicados en el servicio de Interne que incluirá un análisis de fórmulas metafóricas en todos los campos o dimensiones de la vida como el mundo del deporte, el mundo animal, la máquina, la fuerza, o del campo militar, etc. La investigación concluye con una conclusión que incluye los resultados extraídos de la investigación, y la confirmación de las fuentes prácticas y periodísticas del estudio.